So you want to build a BECCS plant: the patchwork policy context for bioelectricity with carbon capture and storage in Europe - Tanzer, Samantha Eleanor; Alvarado Cummings, Susan Caroline; Valenti, Olga Maria; Junginger, Martin; Duden, Anna Sarah (IOP PUBLISHING LTD, 2025)
Bioenergy and Carbon Capture and Storage (BECCS) could produce baseload electricity with reduced net emissionsor even negative emissions—net atmospheric drawdown of CO2—through the permanent storage of captured biogenic CO2, but large-scale deployment remains pending. BECCS is a complex system, combining large-scale biomass sourcing, energy production, and transport and storage of CO2, each subject to a different selection of regulatory frameworks. A BECCS installation also has competing goals; (i) producing and selling energy in a financially viable manner, (ii) providing credible and efficient net removals while minimising other environmental impacts. Navigating these conflicting goals to realize sustainable and economically feasible development of BECCS plants, requires a coherent policy environment. This paper offers a stock-take of the current EU regulatory landscape encountered by potential BECCS facilities, providing recommendations to facilitate BECCS upscaling. Reviewing 19 policies relevant to (parts of) the BECCS system, including legislation in force and under development, non-binding communications and funding mechanisms, assessing whether these policies facilitate or hinder BECCS development. In doing so, we identified a lack of a standardised definition of negative emissions, as well as insufficient clarity on the approach to system boundaries selection to use in emission accounting, sustainability criteria and accounting of upstream emissions for biowastes and residues. Furthermore, clarity regarding the long-term valuation of different types of negative emissions is missing and with it, policies that can enable long-term price stability to allow increased costs of generation practices. We conclude that BECCS is subject to a complex regulatory landscape with limited internalisation of climate value. Financial considerations at plant level as well as competition for biomass have implications for reaching EU climate targets, including the proposed 2040 target of a net-zero power sector with 4-34 Mtpa of BECCS. High-ambition BECCS targets may not be realistic under current regulatory conditions and constrained biomass supply.
Keywords: BECCS; bioenergy with carbon capture and storage; carbon dioxide removal; climate policy; EU policy; negative emissions; power sector; Food Science; General Environmental Science; Agricultural and Biological Sciences (miscellaneous); Geology; Earth-Surface Processes; Atmospheric Science; SDG 13 - Climate Action